Caracterização morfoagronômica, bromatológica e molecular de germoplasma de capsicum spp - Brilhante, Bruna Dias Gomes (2018)
Chilli peppers of the genus Capsicum have economic, nutritional and social significance. The existence of detailed information on the potential of use of the accesses is fundamental for the improvement of plants. In order to begin the development of a breeding program it is necessary to have divergent genetic material, and estimates of genetic diversity are known to better exploit these genetic differences. The objective of this study was to characterize and estimate the genetic diversity among 69 accessions of Capsicum spp. The accessions were collected from Espírito Santo farmers and family agriculture fairs in that state, as well as donations from the UENF (State University of Norte Fluminense). The germplasm collection of the Federal Institute of Espírito Santo (Ifes ), Alegre Campus. The experimental design was a randomized block with 69 treatments and four replications, totaling 276 plants. We used 39 morphoagronomic descriptors (25 qualitative and 14 quantitative), six chemical descriptors and ten Inter Simple Sequence Repeats (ISSR) for molecular characterization. The qualitative variables were submitted to descriptive analysis through fashion and the quantitative and bromatological descriptors submitted to variance analysis, Scott-Knott's grouping of means (1974) and relative importance of characteristics by the method of Singh (1981). The distance matrix of the quantitative variables was obtained by the Mahalanobis distance and the qualitative data by means of the hierarchical methods. To obtain the genetic dissimilarity matrix, based on the ISSR loci, the arithmetic complement of the Jaccard Index was used. Subsequently, a joint analysis of the quantitative and qualitative morphoagronomic variables was performed by Gower algorithm, a cluster for bromatological analysis and another for molecular analysis. Variation was observed for most qualitative characters. For the quantitative morphoagronomic characters and bromatological parameters a significant variation of values was also observed. The ISSR markers were efficient to detect the genetic variability between the accesses, being the marker UENF 04 the most polymorphic. Based on the morphoagronomic, bromatological and molecular characterizations, it was possible to verify high phenotypic and genotypic variability, and all the accesses obtained were considered different. No correlation was detected between the geographic distances and the genetic distances, configuring a lack of structuring between the genetic variability and the collection site, which can be explained by the practice of constant exchanges between the rural producers of the region. The IFCA 31 and IFCA 40 accessions were considered promising for a plant breeding program for ornamental purposes because they presented lower plant height and crown diameter. The IFCA 8 and IFCA 28 accessions of the food processing industry, since they have higher values of soluble solids, implying better sensory characteristics (flavor and aroma). The ISSR markers were efficient to access the genetic variability of the pepper accessions, being possible to observe some correspondences with the morphoagronomic and bromatological characterizations.